Women, the heart of intuition, and creation entanglement - Bradley, Raymond T.; Torris, Chaarenne T. (Frontiers in Psychology, 2025)
Within the broader topic of women's intuition, the focus of this work is mother-offspring intuition—the enigmatic connection between a mother and her offspring, wherein distress or imminent harm is instantly sensed, even when thousands of miles apart. Instant nonlocal communication irrespective of distance, is known as entanglement in quantum physics, and has been repeatedly verified since the 1970′s. Building upon this discovery, a new concept–multiscale entanglement–is postulated to create a two-way micro to macroscale bond of tacit connection between a mother and a fetus, initiated at conception. Nurtured by the mother's unconditional love and mediated by her self-induced state of heart coherence, the process evolves during gestation by entanglement among subatomic and atomic constituents of cells, extending to molecules, organs and so forth to create a tacit bond of ‘inseparability' between their bodies. By the time the offspring has reached adolescence, this relation has often become a two-way psychic bond whereby either can instantly intuit something is amiss or that imminent harm/danger awaits the other. A quantum holographic approach is used to describe the information communication processes involved, in which states of selfless/unconditional love create a psychoenergetic channel for nonlocal communication—of which mother-offspring intuition is one facet. The work is documented with evidence where available, and begins with a review of research on women's intuition. This includes an in-depth examination of a groundbreaking electrophysiological experiment on nonlocal intuition documenting brain and heart response to prestimulus information by gender.